Induction of DKK1 by ox‐LDL negatively regulates intracellular lipid accumulation in macrophages. Issue 1 (28th November 2014) - Zhang, Yu; Ge, Cheng; Wang, Lin; Liu, Xinxin; Chen, Yifei; Li, Mengmeng; Zhang, Mei
Abstract : Dickkopf1 (DKK1), a canonical Wnt/β‐catenin pathway antagonist, is closely associated with cardiovascular disease and adipogenesis. We performed an in vitro study to determine whether oxidized low‐density lipoprotein (ox‐LDL) increased the expression of DKK1 in macrophages and whether β‐catenin and liver X receptor α (LXRα) were involved in this regulation. Induction of DKK1 expression by ox‐LDL decreased the level of lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1) via a Wnt/β‐catenin pathway and increased ATP‐binding cassette transporter A/G1 (ABCA/G1) levels via a signal transducer and activator of transcription 3 (STAT3) pathway. Lower LOX‐1 and higher ABCA/G1 levels inhibited cholesterol loading in macrophages. In conclusion, ox‐LDL may induce DKK1 expression in macrophages to inhibit the accumulation of lipids through a mechanism that involves downregulation of LOX‐1‐mediated lipid uptake and upregulation of ABCA/G1‐dependent cholesterol efflux. Abstract : Ox‐LDL increases the levels of DKK1 via LXRα and β‐catenin in macrophages. DKK1 inhibits lipid accumulation in macrophages. DKK1 increases the levels of ABCA/G1 via STAT3 pathway.